Recommendations on managing lenvatinib and everolimus in patients with advanced or metastatic renal cell carcinoma. Issue 12 (2nd December 2017) - Grande, E; Glen, H; Aller, J; Argenziano, G; Lamas, MJ; Ruszniewski, P; Zamorano, JL; Edmonds, K; Sarker, S; Staehler, M; Larkin, J
ABSTRACT: Introduction : There are several second-line treatment options for patients with renal cell carcinoma after first-line failure of a tyrosine kinase inhibitor, especially with the recent approvals of cabozantinib, nivolumab, and the lenvatinib plus everolimus combination. A lack of reliable biomarkers and an overall lack of prospective head-to-head comparisons make it a challenge to choose a second-line treatment in the clinic. Areas covered : In this review/meta-opinion, we describe the safety profile of the lenvatinib plus everolimus combination in renal cell carcinoma. The combination of lenvatinib plus everolimus has achieved the highest rates of objective responses and the longest progression free and overall survival in cross-comparison trials. At the same time, the safety profile of this combination, including the rate of total and severe adverse events, the percentage of dose reductions required, and the rate of treatment discontinuation, was less favorable compared with available monotherapy options, suggesting that better management could help to maximize the activity of this combination while protecting patients from undue harm. Expert opinion : Herein, we aim to postulate multidisciplinary recommendations on the advice to offer to patients and caregivers before starting treatment and how to manage the combination from the perspective of daily clinical practice.